The ICT Used by the English Lecturers for Non English Study Program Students at STAIN Curup - Apriani, Eka; Hidayah, Jumatul (Vision: Journal for Language and Foreign Language Learning, 2019)
This research is done by the researcher to investigate kinds of ICT used by English lecturers for non-English Study Program students at IAIN Curup and to investigate the roles of ICT for the English lecturer at IAIN Curup. This research used descriptive quantitative Because the questioner's results were evaluated and explained in the explanatory form.The questionnaire used as the instrument to collect the data. Questionnaire about the ICT used by the English lecturers for non-English Study Program students at IAIN Curup and the role of ICT for English Lecturer. Five processes is used to analyze the data from questionnaires in this research. They are (1) data managing of research result, (2) reading/memoing of result, (3) description of result; (4) classifying of research result and (5) interpreting of research result. The result showed that the lecturers always used three types of ICR in teaching English in the classroom, they were the speaker, educational games, and website resources. The reason for them using three types of ICT because it was easy to use and cheap. In using the ICT, the lecturers have a different opinion about About ICT's role in promoting its learning operations. The use of ICT in the teaching and learning system had 7 (seven) roles. It is about the role of ICT in motivating, attracting, and enhancing the success of learners in studying English.